SOSIALISASI DAN PELATIHAN BIJAK BERMEDIA SOSIAL MEDIA AGAR TERHINDAR DARI JERAT UU ITE BAGI SISWA/SISWI MADRASAH ALIYAH DARUD DA'WAH WAL IRSYAD (DDI) PANGKEP - Alwi, Erick Irawadi; Hasanuddin, Tasrif (Devote: Jurnal Pengabdian Masyarakat Global, 2023)
Students become the next generation of the nation and the state must know how to utilize technology properly. Not all students have an understanding of how to be wise with social media to avoid the snares of the ITE Law, not a few students do not understand the legal risks of applying the ITE Law, including students of Madrasah Aliyah Darud Da'wah Wal Irsyad Pangkep. For this reason, socialization and training on Wise social media and ITE Law are needed so that students of Madrasah Aliyah Darud Da'wah Wal Irsyad Pangkep can avoid the legal traps of the ITE Law. The method used in this service is in the form of socialization and training in providing education to students of Madrasah Aliyah Darud Da'wah Wal Irsyad Pangkep. The results of measuring the level of understanding before socialization were carried out pre-test with results of 40.8% and post-test after socialization of 90.6% of these results can conclude that community service activities have increased student understanding related to Wise social media to Avoid the Snares of the ITE Law by 49.8%.